HIGH TEMPERATURE RESEARCH OF THE FEATURES OF THE LOW-VOLTAGE POTENTIAL INFLUENCE ON THE BEHAVIOR OF THE SLAG-METAL BATH AT TOP BLOWING (Modern Problems of Metallurgy, 2019)
Despite the long period of existence and comprehensive research, the oxygen-converter process has high potential for improving technical and economic indicators, which makes it relevant for studies aimed at solving problems of increasing production efficiency and resource saving.Numerous industrial experiments in 60-ton, 160-ton and 250-ton converters during the periods of mastering the method of low-voltage potentials application to the lance and metal melt, designed in ISI NASU, showed the possibility of improving a number of important technological parameters of steel smelting.The paper considers the results of laboratory high-temperature researches on oxygen converter model with top blowing of effects, arising when an electric current passes through an electrical circuit a lance-steelmaking bath at low-voltage potential application of negative or positive polarity to the lance and opposite polarity to the bottom contact electrode in comparison with heats, conducted without electric influence.The trends revealed in industrial converters were confirmed: according to the effect of positive polarity on the lance on the temperature of the bath and on the leading role of the character and intensity of the slag formation process on the level of the current in the chain lance- converter bath. There was also a difference in the brightness of the zone of interaction between the oxygen jet and the slag-metal melt according to the studied options, corresponding to the heat content of the bath: the brightest glow of the sublance zone was observed at the application of positive polarity to the lance, and the weakest glow on comparative heats.By analyzing the video materials, the alternating character of the foaming and gone of the slag phase during the course of the blowing was revealed, that characterized by the opposite direction for the two polarities of the applied potential. It was also noted that the heats carried out with the positive polarity of the potential on the lance differed by a low level of formed splashes of metal and slag, despite the smallest visual amount of the slag phase. And the smallest level of metal splashes was visually noted in the option of application of negative polarity to the lance. It was also revealed that blowings with negative polarity application to the lance differed by earlier liquid slag formation with the highest level of its rise.A specific effect was revealed on the influence of the potential polarity on the surface of the slag phase compared with the option without effects: the formation of local high bursts in the form of “columns” at negative polarity on the lance and “viscous” boiling with an intense output of CO torches on the surface at a positive polarity on the lance.The effect of the low-voltage potential application on reducing the level of metal losses with slag was established: with negative polarity at the lance with the metal drops on 5.9 kg/t of steel, and with positive polarity, with iron oxides in the slag on 4.2 kg/t of steel.
Keywords: high-temperature model; oxygen blowing; slag-metal bath; low-voltage potential